VITALISASI SISTEM EKONOMI ISLAM MENUJU KEMANDIRIAN PEREKONOMIAN UMAT - SYAPARUDDIN, SYAPARUDDIN (Islamic Economics and Business Faculty of UIN Antasari, 2013)
The Islamic economic system in the specific characteristics, is very different from the othereconomic systems because it is as an integral part of Islamic system, and economic in Islam brings anequlibrium for individual and public interest, as well as it brings an individual freedom for economicactivities. In the effort of compliting its acknowledgment to economic freedom, Islam gives anauthority to the government to intervere in the fungsionalization of Islamic economic system. Itmeans that all matters which concern on the economic aspects, have been discussed in Islam. So thatit could be concluded that the regulation of economic in Islam, is absolutely complete. Therefore, theapplication of Islamic economic system in the social order of community's economy probably wouldbring prosperity and benefit for community itself.